1992
DOI: 10.1021/jm00082a011
|View full text |Cite
|
Sign up to set email alerts
|

Class III antiarrhythmic activity of novel substituted 4-[(methylsulfonyl)amino]benzamides and sulfonamides

Abstract: The synthesis and Class III antiarrhythmic activity of a series of 4-[(methylsulfonyl)amino]benzamides and sulfonamides are described. Selected compounds show a potent Class III activity and are devoid of effects on conduction both in vitro (dog Purkinje fibers) and in vivo (anesthetized dogs). Compounds having a 2-aminobenzimidazole group were found to be the most potent, and one compound having this heterocycle (5, WAY-123,398) was selected for further characterization. Compound 5 was shown to have good oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 1 publication
(1 reference statement)
0
23
0
Order By: Relevance
“…Benzimidazoles and 2‐aminobenzimidazoles are very powerful compounds because of their applications in therapeutic and biological sciences (Figure ) . These compounds were used as neuropeptide YY1 receptor antagonist, N ‐methyl‐D‐aspartate (NMDA) antagonist, factor Xa(FXa) inhibitor, poly(ADP‐ribose)polymerase (PARP) inhibitor and non‐peptide thrombin inhibitor .…”
Section: Figurementioning
confidence: 99%
“…Benzimidazoles and 2‐aminobenzimidazoles are very powerful compounds because of their applications in therapeutic and biological sciences (Figure ) . These compounds were used as neuropeptide YY1 receptor antagonist, N ‐methyl‐D‐aspartate (NMDA) antagonist, factor Xa(FXa) inhibitor, poly(ADP‐ribose)polymerase (PARP) inhibitor and non‐peptide thrombin inhibitor .…”
Section: Figurementioning
confidence: 99%
“…1517 Amination of 13a with 3-aminopropanol under neat conditions at high temperature afforded the highly polar intermediate 14a , which required extensive chromatography for purification. (18) It was found that conducting the amination reaction under solvent-free microwave heating conditions at 180 °C/25 min afforded 14a in high yield and purity after simple extraction.…”
Section: Resultsmentioning
confidence: 99%
“…16 Compounds containing this heterobicyclic nucleus exhibit therapeutic properties such as antiarrhythmic, 17 antihistaminic, 18 anticancer, 20 and antiviral, 21 to name just a few of them. In addition, benzimidazoles also show diverse biological activities as inhibitor of phosphodiesterase IV, 22 or antagonist of angiotensin II 23 and neuropeptide Y 24 receptors.…”
Section: Methodsmentioning
confidence: 99%